Concluding remarks [In A thriving agricultural sector in a changing climate: Meeting Malabo Declaration goals through climate-smart agriculture] - De Pinto, Alessandro; Ulimwengu, John M. (International Food Policy Research Institute, 2017)
The ATOR concludes with Chapter 12, which highlights key policy recommendations for the CAADP/Malabo agenda. Finally, the report’s appendixes provide aggregate-level data on the CAADP indicators, organized by geographic regions, regional economic communities, economic characteristics, and CAADP groups, showing when a CAADP compact was signed or the level of CAADP implementation reached.